Therapy influences goal attainment following botulinum neurotoxin injection for focal spasticity in adults with neurological conditions. (7th June 2018) - Moore, Elizabeth Jane; Olver, John; Bryant, Adam Leigh; McKenzie, Dean Philip; Williams, Gavin
ABSTRACT: Objective : To determine whether therapy influenced goal attainment following botulinum toxin (BoNT-A) injection for focal spasticity in adults with neurological conditions. Methods : A prospective observational cohort study conducted in a large metropolitan spasticity clinic on adults with focal spasticity of any origin. Participants were provided with a therapy programme, designed to maximise therapeutic outcome. The primary outcome measure was Goal Attainment Scaling. To measure adherence, participants completed a therapy-recording tool each day. Goal attainment, and the rate of adherence to the therapy programme, was evaluated after 10 weeks. Results : Active indications for BoNT-A treatment made up the majority of the goals (80.30%). Goals were achieved in 43/76 cases (56.60%; 95% CI = 42.40 to 69.80%). Therapy adherence was associated with significantly greater goal attainment (OR = 1.02, p = 0.03, 95% CI = 1.00 to 1.04). Greater adherence to therapy increased the odds of goal achievement for active indications but not for passive indications, suggesting a possible statistical interaction between the indication for injection and adherence to therapy ( p < 0.01). Conclusion : Therapy adherence was associated with greater goal attainment. Active indications for BoNT-A were more reliant on adherence to prescribed therapy programmes than passive indications, although further investigation is required.